Daily Consumption of Lipid-Based Nutrient Supplements Containing 250 μg Iodine Does Not Increase Urinary Iodine Concentrations in Pregnant and Postpartum Women in Bangladesh. Issue 8 (14th June 2017) - Mridha, Malay K; Matias, Susana L; Paul, Rina Rani; Hussain, Sohrab; Khan, Md Showkat Ali; Siddiqui, Zakia; Ullah, Barkat; Sarker, Mostofa; Hossain, Mokbul; Young, Rebecca T; Arnold, Charles D; Dewey, Kathryn G
Abstract: Background: Maternal iodine deficiency during pregnancy and lactation is common in Bangladesh. Objective: We evaluated the effect of lipid-based nutrient supplements for pregnant and lactating women (LNS-PL) on urinary iodine concentration (UIC). Methods: We conducted a cluster-randomized controlled effectiveness trial in which we enrolled 4011 pregnant women at ≤20 gestational weeks. Women in 48 clusters received iron and folic acid (IFA; 60 mg Fe/d + 400 μg folic acid/d) and women in 16 clusters received LNS-PL (20 g/d, 118 kcal) containing 22 vitamins and minerals (including 250 μg I). We randomly selected a subsample of 1159 women for repeated urine sample collection, i.e., at enrollment, at 36 wk of gestation, and at 6 mo postpartum, for UIC analysis, a secondary outcome of the trial. Results: The geometric mean UIC at 36 wk of gestation and at 6 mo postpartum did not differ significantly between the IFA and LNS-PL groups. The median (quartile 1, quartile 3) UIC at 36 wk was 27.4 μg/L (16.9, 52.7 μg/L) in the IFA group and 30.2 μg/L (17.7, 56.6 μg/L) in the LNS-PL group; at 6 mo, these were 23.0 μg/L (10.0, 45.9 μg/L) in the IFA group and 22.2 μg/L (9.1, 50.4 μg/L) in the LNS-PL group. Conclusion: Daily consumption of LNS-PL containing 250 μg I did not increase the UICs of pregnant and lactating women in Bangladesh. Iodine from lipid-based nutrient supplements may have been stored in the thyroid gland or secreted in breast milk instead of being excreted in urine. Additional research that uses other biomarkers of iodine status is needed to determine how to meet the iodine requirements of pregnant and lactating women in Bangladesh and similar settings. This trial was registered at clinicaltrials.gov as NCT01715038.